Hubungan Stresor Lingkungan Terhadap Tingkat Kecemasan Pasien ICU - Ridho Pangestu; Mugi Hartoyo; Sherly Metasari; Budiyati Budiyati (Poltekkes Kemenkes Kalimantan Timur, 2024)
Environmental stressors in the ICU cause psychological problems for patients, such as anxiety. Anxiety that is not treated further can hinder the patient care process. This study aims to analyze the relationship between environmental stressors and the anxiety level of patients treated in the ICU. This research is a descriptive correlational study with a cross sectional approach, involving 36 critical patients using a purposive sampling technique. Data were collected using the Intensive Care Unit Environmental Stressors Scale (ICUESS) questionnaire and the Hospital Anxiety and Depression Scale (HADS) questionnaire. Bivariate analysis using SPSS 25 with the Pearson Product Moment test. The results showed three ICU environmental stressors with the highest scores, namely seeing family and friends for only a few minutes every day (128), not being able to sleep (125), and not knowing when your treatment will be finished (115). Most of the patients experienced severe anxiety, 12 people (33.3%). The research results show that there is a relationship between environmental stressors and anxiety levels (p value = 0.000) with the strength of the relationship being strong and in the same direction (r = 0.788). The conclusion of the research is that environmental stressors are related to the patient's anxiety level.